Exploration of Factors that Hinder The Use of Sharia Crowdfunding Model Financing Services as Funding by Micro, Small, and Medium Enterprises (MSMEs) - Azhar Alam; Muchamad Rizsal Sulistiyanto; Aditya Nurrahman; Afief El Ashfahany; Adi Saifurrahman (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
Sharia crowdfunding can be an alternative financing solution with looser requirements than banking, but the reality is that MSMEs using sharia crowdfunding is still relatively low. This study explores the factors that prevent MSMEs from using Sharia crowdfunding financing to meet business capital needs. This research focuses on the level of understanding of MSME entrepreneurs towards Sharia crowdfunding financing and what are the causes of using the sharia crowdfunding model financing to help the capital of MSME actors engaged in food and beverage. This type of research is a survey. This study used two data collection methods, namely filling out questionnaires and in-depth interviews with 12 MSME entrepreneurs in the Surakarta area, then the results were carefully analyzed to find the right results. The findings of this study show that the answer to the level of understanding of MSME actors towards Sharia crowdfunding financing is divided into three, namely, not understanding, understanding a little, and very understanding. This study also shows five facts that prevent MSME actors from using Sharia crowdfunding financing: lack of information and knowledge, still relying on traditional financing, not requiring financing, the impact of the pandemic, and a wrong understanding of the working mechanism of sharia crowdfunding. This study is expected to be a reference in the policy of digitizing sharia capital sources for MSMEs.